Mediation of academic self-efficacy between emotional intelligence and academic engagement in physical education undergraduate students - Baños, Raúl; Calleja-Núñez, Juan José; Espinoza-Gutiérrez, Roberto; Granero-Gallegos, Antonio (Frontiers in Psychology, 2023)
The aim of this study was to analyze academic self-efficacy as a mediator between emotional intelligence and academic engagement. A non-experimental, cross-sectional, correlational-causal study was designed in which 1164 Mexican students participated (Mage=21.21; SD=3.26) (30.0% female; 69.6% male; 0.4% other). The scales of emotional intelligence, academic self-efficacy and academic engagement were used, and a structural equation analysis with latent variables was conducted. The results obtained demonstrate that emotional clarity and repair have a positive and direct effect on academic self-efficacy. In addition, emotional repair predicts behavioral and emotional engagement. It was also found that academic self-efficacy is an excellent mediator between emotional clarity and repair, and the dimensions of academic engagement, as it substantially improves behavioral and emotional engagement while decreasing behavioral and emotional disaffection